ANALISIS KETERKAITAN ANTARA INDEKS PEMBANGUNAN MANUSIA DAN PDRB PER KAPITA DI INDONESIA - Ryan Ezkirianto; Muhammad Findi Alexandi (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2013)
This paper attempts to analyse the two-way relationship between human development and economic growth for 33 provinces in Indonesia during six years period: 2006–2011. The various links in each variabel were analyzed with description analysis, such education, government spending on health and education, total government expenditure, income distribution, and density. The quantitatif analysis used two-stage least square (2SLS) method.  The result shows that there is a strong positive relationship between human development index and GDRP per capita, while education, government spending on health and education, total government expenditure, and income distribution are the important links determining the strength of relationship between human development and economic growth. Keywords: human development, economic growth